Analisis Kesulitan Siswa dalam Menyelesaikan Soal Persamaan Linear Satu Variabel Melalui Penggunaan Alat Media - Radiatul Adawiah (STKIP Paris Barantai, 2020)
This study aims to determine (1) Student learning outcomes on the use of audio visual media in learning one variable linear agreement. This research was conducted in 2 cycles. Subjects were 20 semester students in the 2019/2020 academic year. Data were analyzed and collected based on quantitative data and qualitative data. Qualitative data consists of observations of students in the learning process while quantitative data consists of student learning outcomes data that is analyzed by percentage techniques at each meeting. Based on the initial reflection, class action research is carried out with planning, designing evaluation-evaluation instruments to learn the frequency of student activities, to study the development of process skills at the KBM, and to measure students' ability to learn Linear Equation for One Variable. The results showed that the learning test results obtained by students in the first cycle were 61.10% with an average value of 6.80 and in the second cycle of 86.09% with an average of 7.60. Keywords: Learning Outcomes of One Variable Linear Equation, Audio Visual Media.